The impact of mobile devices on the shopping experience - Cavalinhos, S. (2018)
The use of mobile devices, such as the mobile phone, has changed the way we live our everyday life, is part of our culture, and the access to information is done anytime and anywhere. This is a new opportunity for the retailers to influence shoppers’ attitudes and behaviours. The present research aims to understand why, how and when do shoppers use mobile devices as their shopping assistance, and as result, what happens when they do. Do shoppers have better shopping experiences? A qualitative and quantitative research design is needed to explore this issues and teste the conceptual model. It’s expected that this research will allow to understand shoppers’ motivations and behaviours and fulfil the gap in the knowledge of the impact of new technologies in shopping experience.